One approach for advanced internet-programs creation on example of widget-programs developing - Glybovets, M.M.; Koval, I.V.; Koren, O.M. (PROBLEMS IN PROGRAMMING, 2025)
Considers use of methodology for advanced internet-programs creation on base of Adobe Flex 2.0, using design patterns and architecture shell. Approach illustrated by developing widget-programs.Problems in programming 2011; 4: 49-55